2008
DOI: 10.3390/s8020830
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated GIS-Expert System Framework for Live Hazard Monitoring and Detection

Abstract: In the context of hazard monitoring, using sensor web technology to monitor and detect hazardous conditions in near-real-time can result in large amounts of spatial data that can be used to drive analysis at an instrumented site. These data can be used for decision making and problem solving, however as with any analysis problem the success of analyzing hazard potential is governed by many factors such as: the quality of the sensor data used as input; the meaning that can be derived from those data; the reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…As Noy and Guinness (2001) point out, programmers make design decisions based on the operational properties of a class, whereas an ontology designer makes these decisions based on the structural properties of a class. In consequence, we are still short of ontologies of geographic processes, and ontologies are much easier translated into a database schema than into process models – although the most recent crop of articles (Klien and Probst 2005, Lemmens et al 2007, Peachavanish and Karimi 2007, McCarthy et al 2008) attempts to address the problem.…”
Section: State Of the Art: In Theorymentioning
confidence: 99%
“…As Noy and Guinness (2001) point out, programmers make design decisions based on the operational properties of a class, whereas an ontology designer makes these decisions based on the structural properties of a class. In consequence, we are still short of ontologies of geographic processes, and ontologies are much easier translated into a database schema than into process models – although the most recent crop of articles (Klien and Probst 2005, Lemmens et al 2007, Peachavanish and Karimi 2007, McCarthy et al 2008) attempts to address the problem.…”
Section: State Of the Art: In Theorymentioning
confidence: 99%
“…Compared to the results obtained in Vrandecic (2010) for the ontologies in the Watson EA corpus (a subset of the Watson corpus that is part of the Billion Triple Challenge data) (Maynard & Harth, 2012), it can be observed that the values of R^ are consistent with those of the ontologies in the corpus (lower than 0.5), whereas the values of R VNS and N NS are not consistent since they are expected to be lower than 5 and greater than 10, respectively.…”
Section: Vocabulary Evaluationmentioning
confidence: 99%
“…Filtered, clean information is sent to the application, which is the GIS, installed in the host computer at the monitoring center. The GIS is readily accessible to the authorities, making this system user-friendly [21,37,38]. The sharing of data starts when the RFID devices interact with each other.…”
Section: Rfid and Communication Technologies Functional Flowmentioning
confidence: 99%